Beyond NK Cells: The Expanding Universe of Innate Lymphoid Cells - Cella, Marina; Miller, Hannah; Song, Christina (Frontiers in Immunology, 2014)
For a long time NK cells were thought to be the only immune innate lymphoid population capable of responding to invading pathogens under the influence of changing environmental cues. In the last few years, an increasing amount of evidence has shown that a number of different Innate Lymphoid Cells found at mucosal sites rapidly respond to locally produced cytokines in order to establish or maintain homeostasis. ILC populations closely mirror the phenotype of adaptive Thelper subsets in their ability to secrete soluble factors. Early in the immune response, ILCs are responsible for setting the stage to mount an adaptive T cell response appropriate to the incoming insult. Here we review the diversity of ILC subsets and discuss similarities and differences between ILCs and NK cells in function and key transcriptional factors required for their development.